INVENTARISASI VEGETASI PADA DAERAH RAWAN KEBAKARAN DI DESA LUKUN, TEBING TINGGI TIMUR, KABUPATEN KEPULAUAN MERANTI, PROVINSI RIAU - Meyla Suhendra; Nur Suhada; Perijal Chandra Damanik; Dinda Kurnia Shafitri; Khairuniah Khairuniah (Jurnal Penelitian Ekosistem Dipterokarpa, 2021)
Lukun is one of the village are located in Tebing Tinggi Timur sub-district, Meranti Island district, Riau Province. Generally, Lukun people lived as a farmer of Rubber, Sago and fisherman. The aims of vegetation analysis in this research is to identified landfire area. This method is called Vegetation analysis and is commonly used in analyzing the condition of a land based on the type of plant found. In general, the components of plants that vegetation consist is shrubs, epiphytes, ferns, palm, vines, herbs and trees. The result shown that fire prone area to burning area is dominated by swamp shrubs. In different area, especially in village forest was dominated by woody plant. This area was categorized to low risk lo fire prone.